Fibrin structural and diffusional analysis suggests that fibers are permeable to solute transport. (1st January 2017) - Leonidakis, Kimon Alexandros; Bhattacharya, Pinaki; Patterson, Jennifer; Vos, Bart E.; Koenderink, Gijsje H.; Vermant, Jan; Lambrechts, Dennis; Roeffaers, Maarten; Van Oosterwyck, Hans
Graphical abstract: Abstract: Fibrin hydrogels are promising carrier materials in tissue engineering. They are biocompatible and easy to prepare, they can bind growth factors and they can be prepared from a patient's own blood. While fibrin structure and mechanics have been extensively studied, not much is known about the relation between structure and diffusivity of solutes within the network. This is particularly relevant for solutes with a size similar to that of growth factors. A novel methodological approach has been used in this study to retrieve quantitative structural characteristics of fibrin hydrogels, by combining two complementary techniques, namely confocal fluorescence microscopy with a fiber extraction algorithm and turbidity measurements. Bulk rheological measurements were conducted to determine the impact of fibrin hydrogel structure on mechanical properties. From these measurements it can be concluded that variations in the fibrin hydrogel structure have a large impact on the rheological response of the hydrogels (up to two orders of magnitude difference in storage modulus) but only a moderate influence on the diffusivity of dextran solutes (up to 25% difference). By analyzing the diffusivity measurements by means of the Ogston diffusion model we further provide evidence that individual fibrin fibers can be semi-permeable to solute transport, depending on the average distance between individual protofibrils. This can be important for reducing mass transport limitations, for modulating fibrinolysis and for growth factor binding, which are all relevant for tissue engineering. Statement of Significance: Fibrin is a natural biopolymer that has drawn much interest as a biomimetic carrier in tissue engineering applications. We hereby use a novel combined approach for the structural characterization of fibrin networks based on optical microscopy and light scattering methods that can also be applied to other fibrillar hydrogels, like collagen. Furthermore, our findings on the relation between solute transport and fibrin structural properties can lead to the optimized design of fibrin hydrogel constructs for controlled release applications. Finally, we provide new evidence for the fact that fibrin fibers may be permeable for solutes with a molecular weight comparable to that of growth factors. This finding may open new avenues for tailoring mass transport properties of fibrin carriers.